The Influence of E-Service Quality on Purchase Decision Mediated by Consumer Trust on Blibli E-Commerce Users in Bandung City - Violita Yuyun; Mohamad Hadi Prasetyo (Jurnal Ilmiah Ekonomi dan Keuangan, 2026)
This study aims to examine the effect of e-service quality on purchase decisions mediated by consumer trust among Blibli e-commerce users in Bandung City. This research employs a quantitative approach with descriptive and verification methods. The population consists of Blibli users with an unknown population size, while the sample includes 130 respondents who have used Blibli more than three times, selected using non-probability sampling. Data were collected through questionnaires and analyzed using PLS-SEM with SmartPLS version 4. The results indicate that e-service quality has a positive and significant effect on consumer trust, consumer trust has a positive and significant effect on purchase decisions, and e-service quality has a positive and significant indirect effect on purchase decisions through consumer trust. These findings highlight the importance of improving e-service quality to strengthen consumer trust and purchasing decisions in e-commerce.